A Murine Monoclonal Antibody With Potent Neutralization Ability Against Human Adenovirus 7 - Wang, Rong; Lu, Jiansheng; Zhou, Quan; Chen, Lei; Huang, Ying; Yu, Yunzhou; Yang, Zhixin (Frontiers in Cellular and Infection Microbiology, 2019)
B1-type human adenoviruses (HAdVs) HAdV-3, HAdV-7, and HAdV-55 have caused epidemics in North America, Asia, and Europe. However, to date, no adenovirus vaccines or antiviral drugs have been approved for general use. In this study, an immune library of scFv-phage antibodies was constructed and mouse monoclonal antibody (MMAb) 10G12 was obtained through selection. 10G12 is specific for HAdV-7 through binding the loop1 and loop 2 (LP12) of the hexon, exhibits strong neutralization activity against HAdV-7, and is stable in serum and buffer at different pH values. The findings expand our knowledge of adenovirus and antibody responses and may assist the design of adenovirus vaccines and antiviral drugs.